2013
DOI: 10.2214/ajr.12.9249
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive MRI Features of Pediatric Medulloblastoma Subtypes

Abstract: The LC or anaplastic medulloblastoma subtype was associated with increased ADC and with ring enhancement, the latter of which correlated with tumor necrosis. These features could be considered in the evaluation of high-risk medulloblastoma subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
67
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 35 publications
9
67
0
4
Order By: Relevance
“…Classical MB is typically hypointense on T1W and hyperintense on T2W with restricted diffusion and variable enhancement (4). Anaplastic MB is associated with increased apparent diffusion coefficient (ADC) value and ring enhancement (10).…”
Section: Discussionmentioning
confidence: 99%
“…Classical MB is typically hypointense on T1W and hyperintense on T2W with restricted diffusion and variable enhancement (4). Anaplastic MB is associated with increased apparent diffusion coefficient (ADC) value and ring enhancement (10).…”
Section: Discussionmentioning
confidence: 99%
“…Although medulloblastomas are classically categorized based on the presence of densely packed round cells, pathologic "variants" (large-cell or anaplastic medulloblastoma, desmoplastic medulloblastoma, and medulloblastoma with extensive nodularity) with unique histologic features and biologic or clinical behavior are now recognized and incorporated in the 2007 WHO classification. Investigators have further shown heterogeneous imaging features 46 and marked genetic diversity of medulloblastoma with at least 4 unique molecular subgroups (WNT, SHH, group C, and group D) having distinct transcription profiles, chromosomal aberrations, and clinical behavior. 47,48 Of note, 4 of the 8 medulloblastomas with the highest rTBF (range, 2.16 -4.97) demonstrated the most aggressive behavior, with death occurring within 11 months of tumor diagnosis in 3 patients and the remaining patient classified as having high-risk disease at the time of the study because of leptomeningeal seeding.…”
Section: Discussionmentioning
confidence: 99%
“…6 Specifically, “tumor location” was defined as midline vermian/fourth ventricle, cerebellar hemisphere, or cerebellar peduncle/cerebellopontine angle cistern (CP/CPA). “Tumor margin” was characterized as ill-defined if >50% of the margin could not be distinguished from the surrounding cerebellar parenchyma on the basis of all imaging sequences.…”
Section: Methodsmentioning
confidence: 99%
“…Prior studies have shown that medulloblastomas present with heterogeneous imaging features, including location and enhancement patterns. 6 These phenotypic radiologic features may reflect underlying differences in tumor biology. 7,8 In this study, we hypothesized that distinct MR imaging features predict molecular subgroups of pediatric medulloblastoma.…”
mentioning
confidence: 99%